Indigenous Knowledge in Environmental Assessment - Stevenson, Marc G. (ARCTIC, 1996)
Increasingly, federal environmental guidelines require developers to consider the "traditional knowledge" of aboriginal people in assessing the impact of proposed projects on northern environments, economies, and societies. However, several factors have limited the contributions of traditional knowledge to environmental impact assessment (EIA) in the North, including confusion over the meaning of this term, who "owns" this knowledge, and its role in EIA. The term "indigenous knowledge," which comprises traditional and nontraditional, ecological and nonecological knowledge, is proposed as an alternative that should allow aboriginal people, and the full scope of their knowledge, to assume integral roles in EIA. Experience gained in attempting to give aboriginal people a voice and an assessment role in the diamond mine proposed by BHP Diamonds Inc. at Lac de Gras in the Northwest Territories has led to the development of a multiphased, holistic approach to involving aboriginal people and their knowledge in EIA. Because of their in-depth knowledge of the land, aboriginal people have a particularly important role to play in environmental monitoring and distinguishing project-related changes from natural changes in the environment. However, the strengths of traditional and Western scientific knowledge in EIA will not be realized until both are recognized as parts of a larger worldview that influences how people perceive and define reality. De plus en plus, les lignes directrices environnementales du gouvernement fédéral exigent des responsables de projets de développement qu'ils tiennent compte du «savoir traditionnel» des peuples autochtones en évaluant les incidences des projets à l'étude sur les milieux, les économies et les sociétés nordiques. Toutefois, plusieurs facteurs ont limité la contribution du savoir traditionnel à l'évaluation des incidences environnementales (EIE) dans le Grand Nord, y compris l'ambiguïté entourant le sens de cette expression, la personne qui «détient» ce savoir, et son rôle dans ...